Dinâmica de ovos e larvas de peixes na bacia do Alto Rio Grande, a montante do reservatório de Furnas, Minas Gerais, Brasil - Suzuki, Fábio Mineo (2010)
The concern with a successful recruitment of fish, especially in water courses affected by dams, has led researchers to perform studies focusing on the early life stages of fishes. In the past years, there has been an increasing interest in studying fish eggs and larvae in freshwater environments. Such phases are critical to the successful recruitment of species. Despite the importance of such issue, there are no records concerning this issue in the upper Rio Grande. In order to broaden the knowledge of the fish fauna of the region, three objectives were proposed concerning the study of fish eggs and larvae: (1) analyze the influence of environmental variables on the drift of eggs and larvae, (2) identify spawning and nursery areas as subsidies to identify priority areas for conservation and (3) assess the role of dams and reservoirs as a barrier to downward movement of ichthyoplankton. The influence of abiotic factors on the reproduction of fish in the basin was clearly evident in the analyses concerning the relationships between these factors and the distribution of eggs and larvae in each environment sampled. However, no patterns were observed concerning the influence of these abiotic factors on the ichthyoplankton densities. The areas most influenced by the dams and reservoirs differed their environmental factors from the stretches without such influence. This could possibly be explaining the low number or even the lack of eggs and larvae in these areas. Significantly different densities observed during the day and at night suggest different behaviors between the larvae of the orders Characiformes and Siluriformes. The tributaries in general contributed to the high number of ichthyoplankton. The distribution of developmental stages of eggs and larvae showed the proximity of the spawning sites and the sampled stretch. The tributaries may also be considered important nursery areas due to the presence of areas of development (marginal lagoons) along their water course. Similar results regarding the importance of ichthyoplankton and natural nursery were obtained for the stretches of the Rio Grande located in the borderline of the Furnas reservoir, the Funil dam and upstream of the Camargos reservoir. The number of marginal lagoons and the contribution of ichthyoplankton associated with the percentage of remaining riparian vegetation make the tributaries Aiuruoca and Mortes as well as the stretch of the Rio Grande located between the Furnas and the Funil reservoirs priority areas for conservation actions. The conservation of the remaining lotic stretches of the upper Rio Grande is fundamental for preserving the integrity of the ichthyofauna, which classify such stretches as areas of major priority for conservational actions. Although the stretches upstream the reservoirs have collaborated with the high numbers of eggs and larvae, there were no catches of ichthyoplankton in the stretches immediately downstream the dams. It is possible to infer that the Funil, Itutinga and Camargos dams are acting as barriers to downward movement of ichthyoplankton.